Distribution and Diversity of Bacteria and Fungi Colonization in Stone Monuments Analyzed by High-Throughput Sequencing. - Qiang Li; Bingjian Zhang; Zhang He; Xiaoru Yang (PLoS ONE, 2016)
The historical and cultural heritage of Qingxing palace and Lingyin and Kaihua temple, located in Hangzhou of China, include a large number of exquisite Buddhist statues and ancient stone sculptures which date back to the Northern Song (960-1219 A.D.) and Qing dynasties (1636-1912 A.D.) and are considered to be some of the best examples of ancient stone sculpting techniques. They were added to the World Heritage List in 2011 because of their unique craftsmanship and importance to the study of ancient Chinese Buddhist culture. However, biodeterioration of the surface of the ancient Buddhist statues and white marble pillars not only severely impairs their aesthetic value but also alters their material structure and thermo-hygric properties. In this study, high-throughput sequencing was utilized to identify the microbial communities colonizing the stone monuments. The diversity and distribution of the microbial communities in six samples collected from three different environmental conditions with signs of deterioration were analyzed by means of bioinformatics software and diversity indices. In addition, the impact of environmental factors, including temperature, light intensity, air humidity, and the concentration of NO2 and SO2, on the microbial communities' diversity and distribution was evaluated. The results indicate that the presence of predominantly phototrophic microorganisms was correlated with light and humidity, while nitrifying bacteria and Thiobacillus were associated with NO2 and SO2 from air pollution.